Optimization of methane production from dairy cow manure and germinated papaya seeds using response surface methodology - Doni Abeng; Sutaryo Sutaryo; Agung Purnomoadi; Setio Susanto; Endang Purbowati; Retno Adiwinarti; Rita Purwasih; Tatik Widiharih (Case Studies in Chemical and Environmental Engineering)
This research aimed to evaluate the use of germinated papaya seeds (GPS) as co-substrate with dairy cow manure (DCM) by paying attention to the effect of GPS sprout length. Germination has been proven to increase seed's nutrient quality, however, lack of information models that optimize anaerobic co-digestion threat combinations of these treatments. The study was conducted using batch-type digesters, and central composite design (CCD). Process optimization was carried out using response surface methodology (RSM). The findings showed that the CCD model developed by RSM was significant (p < 0.05) with R2 of 0.6226. The GPS sprout length did not have a significant impact on its methane production (p > 0.05) however, the combination of GPS and DCM had a significant effect (p < 0.05) on methane production. The highest methane yield was predicted to be 413.136 mL/g volatile solid which can be achieved at a GPS sprout length of <3 mm and a combination of GPS and DCM of 50:50 %. The use of GPS as a co-substrate with DCM was able to increase the nutrient content in the final substrate, and the use of GPS with a shorter sprout length allowed many nutrients not to be used for seed growth.